(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The methodology is an entire analysis made systematically and theoretically implemented in the field of study. It contains the principles and objectives of the methodology related to the branch of that knowledge. It encompasses ideas about various phases, paradigms, quantitative models, theoretical studies, and qualitative methods. The concept of the methodology is not to give a solution to your problems, instead of underpinning the steps considered as a solution is marked and processed to calculate the correct result. So this article explains about the different methodologies implemented for solution analysis is briefly explained